The Role of Organizational Commitment in the Influence of Servant Leadership and Perceived Organizational Support on Organizational Citizenship Behavior Among Employees at the Banyumas District Health Office - Pratama, Bintang Rizki; Darmawan, Akhmad; Purnadi, Purnadi; Haryanto, Totok (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the influence of Servant Leadership and Perceived Organizational Support (POS) on Organizational Citizenship Behavior (OCB), with Organizational Commitment as a mediator, among employees at the Banyumas District Health Office. The research employs a quantitative approach with saturated sampling, involving 110 respondents. Data were analyzed using the Structural Equation Modeling - Partial Least Squares 3.0 method to test the relationships between variables. The findings reveal that Servant Leadership, Perceived Organizational Support, and Organizational Commitment have a positive and significant effect on OCB. Additionally, Servant Leadership and POS positively and significantly influence Organizational Commitment. Furthermore, Servant Leadership and POS positively and significantly impact OCB through Organizational Commitment.